Spectrophotometric determination of arsenic in soil samples using 2-(5-bromo-2-pyridylazo)-5-di-ethylaminophenol (Br-PADAP) - Pereira, Simone de Fátima Pinheiro; Ferreira, Sergio Luis Costa; Oliveira, Geiso Rafael; Palheta, Dulcidéia da Conceiçao; Barros, Bruno de Cássio (Eclética Química, 2008)
In this paper, a new, simple and sensitive method for arsenic determination in soil is proposed. This is based on the reduction of silver (I) and iron (III) ions by arsine followed by a complexation reaction of iron (II) with the spectrophotometric reagent Br-PADAP 2-(5-bromo-2-pyridylazo)-5-di-ethylaminophenol. Arsenic determination with a Sandell’s sensitivity of 3.1 10-4 cm-2, linear range from 0.1 μg ml-1 to 2.0 μg ml-1 (r560 = 0.9995), molar absorptivity of 2.45 105 l mol-1 cm-1 and a concentration detection limit of 1.4 ng ml-1 (3s) were obtained using a 10 ml sample volume. Selectivity was increased with the use of EDTA as a masking agent. The proposed method was applied for arsenic determination in the presence of several ions amounts in digested soil samples. The results revealed that antimony (III), mercury (II), germanium (IV), platinum (IV) interferes at all analyzed proportions. The interferences can be easily removed by the use of EDTA. Precision and accuracy obtained were satisfactory with a R.S.D. < 5 %. Recovery of arsenic in soil samples varied from 95.55 to 102.70 % with a mean of 99.63 %. These results demonstrated that the proposed method is applicable for arsenic analysis in different soil samples.